MENINGKATKAN KREATIVITAS GURU SEKOLAH DASAR MELALUI PERMAINAN RAKYAT SUKU MALIND UNTUK PEMBELAJARAN BERMAKNA (MEANINGFUL LEARNING) - Bernadetha Rizki Kaize; Ni Nyoman Rediani; Herrio Tekdi Nainggolan; Yusri Yusri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Learning in schools along the South Papua border is still less meaningful because it has not been integrated with the local cultural context. This Community Service program aims to develop learning based on traditional games of the Malind tribe to realize Meaningful Learning in elementary schools located in the South Papua–Papua New Guinea border area. The program involved 20 teachers and was implemented through three stages: identification and documentation of relevant traditional games, training on designing learning activities based on traditional games, and mentoring the implementation of learning in the classroom. Evaluation was conducted using pretests and posttests in the form of 30 multiple-choice questions to measure improvements in teachers’ understanding. The data were analyzed using gain scores to determine differences between participants’ initial and final abilities. The results showed an increase in teachers’ competence with a gain score of 0.45, categorized as moderate. Learning based on Malind traditional games was also proven to support character development, such as cooperation, sportsmanship, and appreciation of local culture. Therefore, this model has the potential to create Meaningful Learning experiences while preserving local cultural values and is expected to be replicated in other border schools with similar characteristics in the future. ABSTRAK Pembelajaran di sekolah-sekolah wilayah perbatasan Papua Selatan masih belum optimal karena belum terintegrasi dengan budaya lokal yang dimiliki masyarakat setempat. Kegiatan Pengabdian kepada Masyarakat ini bertujuan mengembangkan model pembelajaran berbasis permainan rakyat Suku Malind sebagai upaya mewujudkan Meaningful Learning di SD perbatasan Papua Selatan–Papua Nugini. Program ini melibatkan 20 guru yang dilaksanakan melalui tiga tahapan, yaitu pendataan dan pendokumentasian permainan rakyat yang relevan, pelatihan penyusunan desain pembelajaran berbasis permainan tradisional, serta pendampingan implementasi pembelajaran di kelas. Evaluasi program dilakukan melalui pretest dan posttest berupa 30 soal pilihan ganda untuk mengukur peningkatan pemahaman guru. Data yang diperoleh dianalisis menggunakan gain score guna mengetahui perbedaan kemampuan peserta sebelum dan sesudah kegiatan. Hasil menunjukkan adanya peningkatan kemampuan guru sebesar 0,45 dengan kategori sedang. Selain meningkatkan kompetensi guru, pembelajaran berbasis permainan rakyat Suku Malind juga berkontribusi dalam penguatan nilai karakter, seperti kerja sama, sportivitas, dan kecintaan terhadap budaya lokal. Oleh karena itu, model pembelajaran ini berpotensi menghadirkan pengalaman belajar yang bermakna sekaligus menjaga kelestarian nilai-nilai budaya, serta dapat direplikasi pada sekolah-sekolah perbatasan lain dengan karakteristik yang serupa di masa mendatang